2019
DOI: 10.3390/nu12010105
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Mastitis in a European Multicenter Cohort: Prevalence, Impact on Human Milk (HM) Composition, and Association with Infant HM Intake and Growth

Abstract: Background: Subclinical mastitis (SCM) is an inflammatory condition of the mammary gland. We examined the effects of SCM on human milk (HM) composition, infant growth, and HM intake in a mother–infant cohort from seven European countries. Methods: HM samples were obtained from 305 mothers at 2, 17, 30, 60, 90, and 120 days postpartum. SCM status was assessed using HM Sodium (Na): Potassium (K) ratio >0.6. Levels of different macro- and micronutrients were analyzed in HM. Results: SCM prevalence in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 54 publications
(91 reference statements)
5
29
0
Order By: Relevance
“…On the one hand, a higher milk Na:K ratio was negatively associated with HCAZ attainment in early lactation. This finding is similar to previous research in Guatemala ( 29 ) and globally, which has shown a negative trend between SCM and head circumference ( 12 , 13 ). On the other hand, higher milk IL-8 was positively associated with HCAZ attainment in established lactation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On the one hand, a higher milk Na:K ratio was negatively associated with HCAZ attainment in early lactation. This finding is similar to previous research in Guatemala ( 29 ) and globally, which has shown a negative trend between SCM and head circumference ( 12 , 13 ). On the other hand, higher milk IL-8 was positively associated with HCAZ attainment in established lactation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also found that a higher milk Na:K ratio, consistent with SCM, increased the odds of being underweight in early lactation. This finding confirms previous work in Bangledesh ( 8 ), Zimbabwe ( 9 ), Zambia ( 10 , 11 ), and most recently Europe ( 13 ), where SCM has been associated with reduced infant weight. On the one hand, SCM might lower milk volume, although previous research found that milk intake among infants did not differ for mothers with SCM ( 12 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations